Instability of interactives: The case of interjections in Gorwaa - Andrason Alexander; Harvey Andrew (Open Linguistics)
This article studies the morpho-phonetic instability of interactives through the example of Gorwaa interjections. The analysis of 91 constructions demonstrates that, in Gorwaa, interjections are highly unstable: the number of idiolectal interjections is much larger than that of shared interjections, and the interjections of both sets form clusters – spaces composed of constructions connected through the family resemblance of a formal and functional type. The formal modifications are achieved through prolongation, replication, alternation (of phones/features), and concatenation, and are related to changes in meaning and the polysemy inherent to interjections. Overall, the interjective category is modeled as a dynamic/fuzzy network of related (formally/functionally) constructions. The grammatical profiles of shared and idiolectal interjections are identical and corroborate the validity of the prototype of interjections. The refinements proposed include a preference for [j] over [w], a tendency toward (extra-)high tones and decreasing tonal patterns, the use of gutturals and clicks as the most common extra-systematic sounds and that of clicks as genuine consonants in non-click languages, the iconic foundation of some interjections and their relationship to babytalk, as well as the close relationship of interjections with the |A| place of articulation.